Communication Behavior in Political Life Ethnic Java at Medan - Katimin Katimin; Syukur Kholil; Junaidi Junaidi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Javanese ethnicity is the most ethnic group in Medan City, so politically the opportunity to occupy political positions such as the Regional Head is very large, but until the 2019 elections the Mayor of Medan was never held by the Javanese ethnic group. This study aims to determine and analyze the motives underlying Communication Behavior in Political Life / Political Choice of ethnic Javanese Muslims in Medan. This research uses descriptive qualitative research with a phenomenological approach. Data obtained through interviews and direct observation. The results of the study mentioned that there are 4 motives underlying the behavior of communication in the political life of ethnic Javanese Muslims in Medan, specifically related to political choices, namely religious, economic, competence, and commitment to commitment.